Memukul Dalam Mendidik Anak, Suatu Tinjauan Dalam Hukum Kekeluargaan Islam Dan Pandangan Hukum Positif - Syofiaty Lubis (Universitas Muhammadiyah Sumatera Utara, 2019)
Children are a gift given by Allah SWT. Parents are given a deposit that they must educate well about one thing or another. But it is not uncommon for parents to educate their children in the wrong way, for example by hitting their own children, not only is the child doing it right or wrong as a parent who is not allowed to beat his child. This study aims to see how the phenomenon of parents who educate their children by hitting through the views of Islamic family law and positive laws adopted in Indonesia. This research is a type of normative research that takes data sources based on library data that will be contested with existing rules and then summarized well so that readers can easily understand